QUALITY OF KWETIAW WITH ADDITIONAL DIFFERENT PERCENTAGE OF CANNA (Canna edulis Kerr.) STARCH - Murna Muzaifa; M. Ikhsan Sulaiman; Liyuza Liyuza (Jurnal Agroindustri, 2014)
Research has been  conducted to eximine the possibility of kwetiaw production from canna starch. The aim of this research was to study the effect of canna starch persentage on quality of kwetiaw.  This study used randomized block design with  single factor, the percentage of canna starch which consist of 5 levels : A = 0%, B = 25%, C = 50%, D = 75% and E = 100%. Parameter analyzed were water content, water absorption, cooking loss, color and texture (elasticity)  of kwetiaw. The result showed that water content, water absorption and cooking loss values of kwetiaw tended to increase with increasing of canna starch substitution. Color of kwetiaw was preferred in 25% canna starch substitution and the preference was decrese with increasing of canna starch substitution. The texture of kwetiaw was preferred on 50% canna starch substitution.